Manusia Satu Dimensi di Bangku Sekolah: Analisis Teori Kritis Herbert Marcuse terhadap Pendidikan yang Menjinakkan - Laily Divia Amlati; Khumairo Wardatul Jannah; Rizqi Dwi Cahyati; Jakaria Umro (Journal Innovation In Education, 2026)
Education is fundamentally a vehicle for human emancipation; however, contemporary school institutions often shift their function into pragmatic instruments of ideological domestication. This study aims to analyze the domestication of students' critical thinking in schools through the lens of Herbert Marcuse's Critical Theory on the "One-Dimensional Man". Using a qualitative approach with a library research method, this study performs a content analysis of Marcuse’s theoretical framework, contextualizing it with current literature in the sociology of education. The findings reveal that modern schooling has undergone acute commodification, where knowledge is reduced to economic exchange value and the fulfillment of "false needs" through the fetishism of quantitative academic indicators. This domestication is structurally embedded through technocratic, industrybiased curricula (link and match), standardized mass evaluations, and a hidden curriculum that institutionalizes a bureaucratic culture of obedience. Through the mechanisms of repressive tolerance and uncritical digitalization, schools amputate students' "negative thinking," trigger academic alienation, and eliminate "healthy unhappiness." Ultimately, schools function as ideological factories that mass-reproduce One-Dimensional Mena generation instrumentally and technically capable but ethically and philosophically paralyzed. This study concludes that a radical deconstruction is urgently required by reclaiming classrooms through criticalemancipatory pedagogy to restore the true purpose of schooling in humanizing human beings.